Предмет: Алгебра,
автор: StageZ
1.Вычислите.
а)(√2)^(-2)-(√3)^(-2)
б)5,6+(-0,2)^(-3)
в)10^(-2)+0,1^(-2)
2.Представьте в виде дроби.
а)(x^2-y^2)^(-1)
б)(2x^(-2)+y^(-1)*x^(3)y
в)(2^(-3)+y^(3)*(2+y/2-y)^(-1)
Ответы
Автор ответа:
0
a) (√2)^(-2)-(√3)^(-2) = 1 / (√2)^2 - 1 / (√3)^2 = 1/2 - 1/3 = 3/6 - 2/6 = 1/6
б) 5,6+(-0,2)^(-3) = 5,6 + 1 / (-0,2)^3 = 5,6 - (10^3) / (2)^3 = 5,6 - 1000/8 = 5,6 - 125 = 119,4
в) 10^(-2)+0,1^(-2) = 1/100 + 100 = 100,01
а)(x^2-y^2)^(-1) = 1 / (x^2-y^2)
б)(2x^(-2)+y^(-1)*x^(3)y = 2 / x^2 + x^3 = (2+x^5) / x^2
в)(2^(-3)+y^(3)*(2+y/2-y)^(-1) = (16y^3 - y + 4) / (8(4-y))
Похожие вопросы
Предмет: Математика,
автор: Banhhjhcbjgbjourd
Предмет: Математика,
автор: bakhtiyarov5676
Предмет: Алгебра,
автор: pobedak07
Предмет: Математика,
автор: 238132
Предмет: Математика,
автор: carpet